Introducing a Kantian interpretation of quantum physics : in accordance with Kant's philosophy of science in the Critique of the power of judgment, reinterpreted and reworked with special attention to the supersensible realm - Mc Loud, Willem (Department of Philosophy, 2016)
In this thesis I confront the problem of indeterminism in quantum physics. The first pioneers accepted indeterminism as part of their Copenhagen interpretation and it was incorporated in Von Neumann's formulation (as the "projection postulate"). But how deep does this indeterminism go? With the arrival of quantum physics, the idea that the world is fundamentally deterministic has been shattered. Redhead's work showed that the experimental confirmation of the violation of Bell's inequality means that determinism has broken down; he even formulated a version of the Bell inequality that is not dependent on local hidden variables and showed that the violation thereof negates even what might be called "stochastic" determinism - at least in the framework of the Lorentzian space-time manifold (Redhead 1987:83, 103). With the acceptance of non-determinism as part of our world, we are confronted with the question: How can the possibility of non-determinism be explained and how can it be reconciled with determinism in one coherent conceptualization of the world? I use the philosophy of science that Immanuel Kant developed in the Critique of the Power of Judgment to develop an answer to these questions. In this part of his philosophy of science Kant is concerned with the possibility and conceivability of a spontaneous (albeit effective) causality in nature's producing its products. Kant developed the idea of this causality in analogy to the achievement of human ends, conceptualizing it as a capacity that non-extended wholes and parts have to be realized as parts forming an aggregated whole in nature. An important feature of my approach is that I develop a new interpretation of Kant's philosophy as presented in his well-known Critique of Pure Reason. In contrast with the two-object and twoaspect views in Kantian interpretation, I argue that the noumenal realm refers to an ontologically distinct realm outside nature, problematically assumed. This agrees with Kant's view in the Critique of the Power of Judgment where it is conceptualized as the substratum of nature and forms a central part of his philosophy of science. It is only when the noumenal (supersensible) realm is conceptualized in this manner that spontaneous causality becomes not only logically possible, but also conceivable within the framework of his philosophy. In my Kantian interpretation of quantum physics his concept of nature is taken as referring to the "classical realm" (where the theories of relativity would apply). His non-extended wholes and parts, which belong to the supersensible realm, find application in superpositions of states, which I argue belong to an ontologically distinct realm - the pre-measurement "quantum realm". Since the classical and quantum realms are taken as ontologically distinct realms, there is no contradiction in ascribing two heterogeneous laws, namely of deterministic and spontaneous causality (which is manifest in the reduction of the wave packet), to these realms which are combined in one description in quantum mechanics. In my view spontaneous causality grounds a non-spatiotemporal potentiality which explains why superpositions of states have the ability to collapse to reduced states. I develop these ideas in the framework of the various interpretations of quantum mechanics.